Ethyl 4-chloro-3-nitrobenzoate - Li, Hao-Yuan (International Union of Crystallography, 2008)
In the molecule of the title compound, C(9)H(8)ClNO(4), an intramolecular C—H⋯O hydrogen bond results in the formation of a planar five-membered ring, which is nearly coplanar with the adjacent six-membered ring, the rings being oriented at a dihedral angle of 4.40 (3)°. In the crystal structure, intermolecular C—H⋯O hydrogen bonds link the molecules.